KONTRIBUSI PESANTREN DALAM PERKEMBEMBANGAN STUDI ISLAM - Djasadi Djasadi (PASCASARJANA UNISNU, 2019)
Studies of Pesantren-related texts, an integral part of Indonesian Islam heritage, have been started long time ago. Even, at least in the last twenty years, it attracts interests of not only prominent orientalists, but also Islamists, Indonesianists and students of this traditional institution of Islamic education who turn to be intellectual. However, such studies do not employ philological approach yet.It is indeed through old manuscripts in Pesantren that Ulama?? genealogy of knowledge can be traced back. Hence, it is not surprising if such manuscripts become one of quintessential aspect of Islam in Indonesia. Pesantren and Islamic kingdoms in Indonesia for example can be regarded as two sides of a coin due to its inextricable relationship.The writer argues that the reason why such manuscripts are not studied within philological framework is its overlapping categorization with Javanese and Malay texts in the form of ??babad??, ??serat??, ??tembang?? and others. In addition, such manuscripts and texts also shared the same language and writing systems in the form of Arabic, ??pegon??, ??Jawi?? and local dialects.In this study, conceptualizing philology of ??Pesantren?? is important but initially the limitation of pesantren texts and manuscripts along with its repository must be clearly defined and explicated. Hopefully, this philological study of Pesantren manuscripts can broaden the horizon of Islamic studies of Indonesia and contribute new insights to philology in general.Key words: Islamic studies of Indonesia, philology, Pesantren and manuscripts.